Economic Growth, Transport Energy Consumption and Environmental Quality Nexus: Assessing the Evidence from Nepal - Dahal, Arjun (The Journal of Knowledge and Innovation, 2023)
This paper intends to determine the influence of economic growth and energy use in the transport sector on the degradation of the environment or rise in CO 2 emissions. It is based on secondary data gathered from numerous financial reviews of Nepal and reports from the World Bank. The exploratory and descriptive research designs are applied to investigate the relationship and effect of GDP and transportation energy consumption on the deterioration of environmental quality. The descriptive statistics, correlation analysis, and ordinary least square (OLS) method are used in the study. It has been discovered that the GDP and transportation energy use each have a substantial role in determining environmental quality. The worsening of environmental quality is also observed to increase by 0.2796 and 0.6699 percent for every one percent increase in GDP and transportation energy consumption, respectively. Policymakers may increase spending on energy-efficient transportation, production methods, and renewable energy sources to decrease carbon emissions.